STUDI EKSPERIMENTAL VARIASI TEKANAN MASUK (SUCTION PREASURE) TERHADAP KINERJA POMPA AIR SENTRIFUGAL PADA ALAT PRAKTIKUM MESIN FLUIDA STTI BONTANG - Yano Hurung Anoi; Faiqah Luthfiyyah Fenriyati; Irianto Irianto; Ahmad Yani (LPPM Universitas Bina Bangsa, 2022)
A centrifugal pump is a device or machine for moving liquids from one place to another by using centrifugal force caused by impeller motion and at the same time converting the kinetic energy of the fluid into compressive force on the liquid being moved and takes place continuously while at the same time converting the kinetic energy of the fluid into compressive force. . This study aims to determine the effect of variations in the inlet pressure of the water flow on the performance of centrifugal water pumps. The method used in this study is the experimental method by conducting direct testing of research tools. Based on the results of testing the water pump installation, and based on the research objectives, it can be concluded that the highest pump shaft power value occurs at an inlet pressure of 0.01 kg/cm2 with a value of 0.3093 kWatt, then the highest hydraulic power value occurs at an outlet pressure of 0 .02 kg/cm2 with a value of 0.1380 kWatt, and the highest pump efficiency value occurs at an outlet pressure of 0.04 kg/cm2 with a value of 50.0109%.